(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
This multidisciplinary study (facies analysis, sequence stratigraphy, calcareous nannofossils and carbon stable isotopes) focuses on the Lower to Middle Toarcian succession cropping out in the Coimbra region (Northern sector of the Lusitanian Basin), Portugal. Deposited on homoclinal carbonate ramp, the sampled hemipelagic series, consisting of marl/limestone alternations can be subdivided into three third-order depositional sequences (ST1, ST2 and ST3) characterised by different vertical facies arrangements and palaeontological contents. The sequence boundaries lie within the Polymorphum Zone, around the Polymorphum/Levisoni Zone boundary and in the Bifrons Subzone (Bifrons Zone). The calcareous nannofossils provide a continuos succession of age-significant assemblages, and a useful set of nannobiohorizons that include the LO of Calcivascularis jansae, the LOs of Biscutum grande and Biscutum finchii, and the FOs of Carinolithus cantaluppii, Carinolithus superbus, Discorhabdus striatus and Discorhabdus ignotus. The evolution of the ð13C agrees with the sequential developments of the series because the positive excursions roughly coincide with transgressive depositional phases, whereas a negative trend is observed during regressive phases.